Heat E-Teaching Material Assisted by Augmented Reality and CTL Model to Promote Students' 4C Skills - Hayatur Ridha; Febrian Virijai; Asrizal (LPPM Undiksha, 2024)
The 21st century requires students to adapt and utilize the growing sophistication of technology. The expected 21st century learning is 4C skills to face global challenges. Students' critical thinking and creative thinking skills in physics learning are still low. The solution to the problem is that students need more interactive teaching media in order to increase interest in learning, digital teaching materials with Augmented Reality integrated CTL models are the solution to the problem. The purpose of this study was to determine the needs analysis, validity and practicality of using digital teaching materials with AR integrated with CTL models to improve students' critical and creative thinking skills. This type of research is Research and Development with the Hannafin and Peck development model. Data collection instruments include needs analysis instruments, validation questionnaire sheets and practicality questionnaire sheets. The data analysis techniques used are descriptive, qualitative, and quantitative statistics. Based on the data analyzed, there are three research results. First, the results of needs analysis research which stated that students' critical and creative thinking was still low. Second, the results of product validation with the valid category. Third, the results of product practicality with a very practical category. It is concluded that electronic teaching materials for heat assisted by Augmented Reality and CTL models can be used in learning. Research implications, with electronic teaching materials assisted by AR CTL model, teachers are expected to be able to motivate, guide and direct students in building 4C skills.